Labor Market Sorting in Germany - Bastian Schulz; Benjamin Lochner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper analyzes how workers are allocated to jobs in Germany. Our main contribution is to show how labor market sorting has evolved over time across worker types and how these developments are related to wages and wage inequality. We show direct empirical evidence that wages are not necessarily increasing in the productivity of the firm a worker is matched with. This feature of the data is predicted by theoretical models of labor market sorting (Shimer and Smith, 2000; Eeckhout and Kircher, 2011). We use a structural search model and the identification procedure proposed by Hagedorn et al. (2014) to empirically identify worker and firm rankings as well as the bivariate density of matches in Germany. We compute rank correlations and find that low-type workers have become increasingly sorted into low-type firms in our period of observation (1998-2008), especially out of unemployment. Sorting of high-type workers into high-type firms has, if anything, slightly decreased during our period of observation.
Keywords: J31; J62; J64; 330